Dissociation between the circulating renin-angiotensin system and angiotensin II receptors in central losartan-induced hypertension - Sugawara,A.M. (2002)
Losartan, an AT1 angiotensin II (ANG II) receptor non-peptide antagonist, induces an increase in mean arterial pressure (MAP) when injected intracerebroventricularly (icv) into rats. The present study investigated possible effector mechanisms of the increase in MAP induced by icv losartan in unanesthetized rats. Male Holtzman rats (280-300 g, N = 6/group) with a cannula implanted into the anterior ventral third ventricle received an icv injection of losartan (90 µg/2 µl) that induced a typical peak pressor response within 5 min. In one group of animals, this response to icv losartan was completely reduced from 18 ± 1 to 4 ± 2 mmHg by intravenous (iv) injection of losartan (2.5-10 mg/kg), and in another group, it was partially reduced from 18 ± 3 to 11 ± 2 mmHg by iv prazosin (0.1-1.0 mg/kg), an alpha1-adrenergic antagonist (P<0.05). Captopril (10 mg/kg), a converting enzyme inhibitor, injected iv in a third group inhibited the pressor response to icv losartan from 24 ± 3 to 7 ± 2 mmHg (P<0.05). Propranolol (10 mg/kg), a ß-adrenoceptor antagonist, injected iv in a fourth group did not alter the pressor response to icv losartan. Plasma renin activity and serum angiotensin-converting enzyme activity were not altered by icv losartan in other animals. The results suggest that the pressor effect of icv losartan depends on angiotensinergic and alpha1-adrenoceptor activation, but not on increased circulating ANG II.